Competitive strategy : techniques for analyzing industries and competitors : with a new introduction - Porter, Michael E., 1947- (New York : Free Press, 1998)
"Now nearing its 60th printing in English and translated into nineteen languages, Michael E. Porter's Competitive Strategy has transformed the theory, practice, and teaching of business strategy throughout the world. Porter introduces his three generic strategies - lowest cost, differentiation, and focuswhich bring structure to the task of strategic positioning. He shows how competitive advantage can be defined in terms of relative cost and relative prices, thus linking it directly to profitability, and presents a whole new perspective on how profit is created and divided." "The ideas in the book address the underlying fundamentals of competition in a way that is independent of the specifics of the ways companies go about competing."--BOOK JACKET.
Pt. I. General Analytical Techniques -- Ch. 1. The Structural Analysis of Industries -- Ch. 2. Generic Competitive Strategies -- Ch. 3. A Framework for Competitor Analysis -- Ch. 4. Market Signals -- Ch. 5. Competitive Moves -- Ch. 6. Strategy Toward Buyers and Suppliers -- Ch. 7. Structural Analysis Within Industries -- Ch. 8. Industry Evolution -- Pt. II. Generic Industry Environments -- Ch. 9. Competitive Strategy in Fragmented Industries -- Ch. 10. Competitive Strategy in Emerging Industries -- Ch. 11. The Transition to Industry Maturity -- Ch. 12. Competitive Strategy in Declining Industries -- Ch. 13. Competition in Global Industries -- Pt. III. Strategic Decisions -- Ch. 14. The Strategic Analysis of Vertical Integration -- Ch. 15. Capacity Expansion -- Ch. 16. Entry into New Businesses. App. A. Portfolio Techniques in Competitor Analysis -- App. B. How to Conduct an Industry Analysis.
Originally published: New York : Free Press, c1980.
Includes bibliographical references (p. 383-387) and index.
Keywords: Competition; Industrial management